Students’ Communication Skills and Scientific Literacy Ability in Biology through Guided Inquiry Learning - Amaditha, Firda Febby; Fitri, Siti Gia Syauqiyah; Ekanara, Bambang (International Journal of Biology Education Towards Sustainable Development, 2024)
The guided inquiry learning model, often called guided discovery learning, is an educational approach that emphasizes student engagement and active learning through exploration and problem-solving under the guidance of a teacher as an instructor. Through guided inquiry learning, this research aimed to examine the correlation between students’ communication skills and scientific literacy ability on the environmental pollution sub-concept. The method used in this research was correlational. The participants in this study were the 10th-grade students of a Senior High School in Serang, Banten. The communication students ' communication skills and scientific literacy abilities were measured by observation sheets and essay questions, respectively. The result showed that the communication skills (oral and written) of the students were categorized as good, with a mean value of 82.27. Meanwhile, students' scientific literacy was categorized as moderate, with a mean value of 82.71. Pearson Product Moment correlation analysis showed that there was a very strong correlation between both values, with a correlation coefficient of 0.890. The linear regression test result showed that communication skills contributed to the student's scientific literacy by as much as 79.2%. It is suggested that applying the guided inquiry model could develop communication skills and students' scientific literacy.